Transcriptomic Analysis Provides Insights into the Energetic Metabolism and Immune Responses in Litopenaeus vannamei Challenged by Photobacterium damselae subsp. damselae - Libao Wang; Qiuwen Xu; Zhijun Yu; Zhenxin Hu; Hui Li; Wenjun Shi; Xihe Wan (Fishes)
To explore the molecular mechanisms of the Litopenaeus vannamei response to infection by Photobacterium damselae, reveal its immune response and energetic metabolic effect, and provide a valuable genetic data source for the scientific prevention and control of Vibrio infection, transcriptomic analysis, RT-qPCR, and physiological and biochemical tests were conducted. The results showed that the expression of key genes involved in lipid and carbohydrate transport, such as apolipoprotein and TPS, was upregulated after pathogenic infection, which brought the accumulation of triacylglycerol and trehalose into the hemolymph. Additionally, the pathogenic infection selectively triggered an immune response in infected L. vannamei, activating certain immune pathways, such as the serpins and MAPK pathways. The pathogenic infection suppressed the activity of phenoloxidase (PO), and the prophenoloxidase (PPO) cascade responses were suppressed by the invasive bacteria. This paper will help us understand the energetic metabolism, immune response, and activation of the immune recognition response after pathogenic infection by P. damselae, and it lays a theoretical foundation for the biological prevention and control of P. damselae infection.